EFEKTIVITAS TERAPI MUSIK KLASIK TERHADAP KUALITAS TIDUR PASIEN DI INTENSIVE CARE UNIT (ICU) RS PELITA ANUGERAH MRANGGEN DEMAK (Nursing Care Journal, 2024)
Background : Patients undergoing treatment in the Internsive Care Unit ( ICU) will experience sleep quality disturbances caused by separates stressors such as noise levels from equuipmet, light, determination of diagnostic measures, providing interventional therapy, mechanical ventilation, medication and critical illness itself . Classical music therapy is proven to have a significant effect on someone who listens to it, fells that they get a calmer and more relaxed felling and reduces fellings of worry. Sleep quality is very important to the wold of health ,especialy for patients who are under treatment, especialy in the ICU, poor sleep quality can result in decreased ability to concentrate,make decisions and participate in daily activities and cause increased sensitivity to irritability.General Phurpose : This study was to determine the effectiveness of classical music therapy on sleep quality of patients in the Intensive Care Unit ( ICU). Experiences methode : used methode by Pre-Experimental Designs One Group Pre & Post test. Methode in used sampling with purposive methode from 30 respondens with used quesionering( Pittsburgh Sleep Quality Index ) PSQI.Research result : classical music therapy can improve sleep quality in order to reduces stress level in Pelita Anugerah Hospital by test wilcoxon showed P value in 0,003 its means classical music therapy is efeective in the sleep quality of patients in Intensive Care Unit ( ICU) Pelita Anugerah Hospitals Mranggen Demak.